Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.2807/ese.16.44.20004-en
|View full text |Cite
|
Sign up to set email alerts
|

Influenza surveillance during the post-pandemic influenza 2010/11 season in Greece, 04 October 2010 to 22 May 2011

Abstract: In this manuscript, we summarise the experience of Greece during the post-pandemic influenza season 2010/11 from 04 October 2010 to 22 May 2011. The spread of the disease and its impact were monitored using multiple surveillance systems, such as sentinel surveillance, virological surveillance and all-cause mortality surveillance. We also focus on the characteristics of laboratory-confirmed severe influenza cases who required admission to an intensive care unit (ICU) (n=368), and/or with a fatal outcome (n=180)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(4 citation statements)
references
References 21 publications
1
1
0
2
Order By: Relevance
“…On the other hand, during the following season, the timing of influenza circulation returned to the pattern observed during the previous interpandemic period, so that the peak of its circulation was completely overlapped with the one of RVA 17 . As reported in previous studies conducted in Europe and Italy, the severity of clinical illness and the hospitalization rate of children in the first post‐pandemic influenza season was comparable or even higher than during the pandemic 18,19 …”
Section: Discussionsupporting
confidence: 77%
“…On the other hand, during the following season, the timing of influenza circulation returned to the pattern observed during the previous interpandemic period, so that the peak of its circulation was completely overlapped with the one of RVA 17 . As reported in previous studies conducted in Europe and Italy, the severity of clinical illness and the hospitalization rate of children in the first post‐pandemic influenza season was comparable or even higher than during the pandemic 18,19 …”
Section: Discussionsupporting
confidence: 77%
“…other European countries such as the UK or Greece [15,16]. Indeed, in France, national data indicated that the 2010-2011 outbreak was moderate compared to the pandemic [13].…”
Section: Original Articlementioning
confidence: 99%
“…2011-12 (30) I( 4) S( 26) N( 22) Επιδηµιολογικές µελέτες για τη µεταπανδηµική περίοδο του 2011 [Athanasiou et al, 2011] κατέδειξαν την αύξηση στη νοσηρότητα της νόσου λόγω επανεµφάνισης του πανδηµικού στελέχους. Για την αντιµετώπιση των σοβαρών περιστατικών γρίπης ήταν αναµενόµενη η κατακόρυφη αύξηση στη χρήση της οσελταµιβίρης για θεραπευτικούς και προφυλακτικούς σκοπούς [ECDC, 2014].…”
Section: προσδιορισµός τιµής Ic50 -αναστολή νευραµινιδάσηςunclassified